A constituição da identidade profissional docente: formação e saberes - Spengler, Míriam Raquel Nilson Backes (Universidade do Vale do Rio do Sinos, 2010)
This study aimed to answer the question How the teacher as a subject constitutes (her)himself as a teacher. To understand the problem, aspects of training and teacher knowledge were studied based mainly on Tardif, Cunha, Gauthier, Pimenta and Garcia. The central axis of the work revolved around the identity and the teacher professional identity that were based on theoretical studies of Nóvoa, Huberman, Lopes, Bauman, Dubar and Arroyo. The field study was conducted with teachers in primary grades with the use of written narratives in which they were provoked, through images, to write. To help in understanding the problem the following questions were proposed: Who is the teacher who teaches in the primary grades? What is his/her professional identity? How did he/she become the professional he/she is? What are the impacts of the training of this professional in his/her practice and in building his/her identity? The analysis pointed to the importance of experiential knowledge in the formation of teacher identity.
Keywords: formação docente; narrativas; identidade profissional docente; narratives; teacher training; professional identity; Ciências Humanas